Approaches to the Economics of Climate Change: A Survey of Literature - Anna Farina Poerbonegoro (Bina Ekonomi, 2016)
This paper is aimed at providing basic underlying principles in viewing the climate change paradigm, focusing on economic approaches necessary to analyze the issue. Economic approaches include market as well as non-market approaches. This distinction is deemed important as many efforts related to adaptation and mitigation to climate change often neglects the mechanism. Keywords: climate change, economic approaches, market approach, non-market approach.